2017
DOI: 10.1002/joc.5311
|View full text |Cite
|
Sign up to set email alerts
|

Changes in extreme precipitation in the Yangtze River basin and its association with global mean temperature and ENSO

Abstract: Extreme precipitation events may lead to secondary disasters such as floods, landslides and erosion. The Yangtze River basin (YRB), which is home to a large population, is susceptible to flooding associated with heavy rainfall. Many dams have been constructed or planned for in the YRB. Understanding the changing behaviour of extreme precipitation and its relationship with other climatic factors will increase planners' ability to plan for, manage and respond to related flood events. This study investigated the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(12 citation statements)
references
References 73 publications
1
11
0
Order By: Relevance
“…The results of trend analysis in this study are generally in accordance with previous studies (Su et al ., 2006; Lü et al ., 2017) that the Rx1day and Rx3day show positive trends in the downstream of the YRB. However, it should be noted that some inconsistencies are found too.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The results of trend analysis in this study are generally in accordance with previous studies (Su et al ., 2006; Lü et al ., 2017) that the Rx1day and Rx3day show positive trends in the downstream of the YRB. However, it should be noted that some inconsistencies are found too.…”
Section: Discussionmentioning
confidence: 92%
“…Lü et al . (2017) demonstrated that there is a significant negative correlation between December–January–February annual and seasonal maximum daily precipitation and El Niño‐Southern Oscillation (ENSO). The aforementioned studies mainly concentrate on exploring the relationships between climate indices and extreme precipitation in the YRB at seasonal or annual scale.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the above analysis, extreme precipitation (P95 and E-NE) has changed significantly in the mean and distribution from the cooling to warming environment. Lü et al (2017) found the global temperature played more roles in affecting extreme precipitation (daily maximum precipitation) than local temperatures in the Yangtze River Basin [60]. Figure 9 plotted the changes in the precipitation amount for nine precipitation intensities responding to per 1 °C increase in global surface temperature from 1959 to 2013 (∆ /∆ ).…”
Section: Changes In P95 E-ne Andmentioning
confidence: 99%
“…According to previous studies, the SPI-3 is normally used to assess agricultural droughts, SPI-6 is important in studying hydrological droughts while the SPI-12 and SPI-24 are used in detecting groundwater droughts (Elkollaly et al 2018). This method is recommended by the World Meteorological Organization (Lü et al 2017) (Svoboda and Fuchs 2017b) and is widely used for drought analysis. Detailed information about the method is much explained in previous studies (Ayuso et al 2015;Du et al 2013;Elkollaly et al 2018;Zhim et al 2019).…”
Section: Standardized Precipitation Index (Spi)mentioning
confidence: 99%